The development of Paleozoology Science in the era of the victory of evolutionism (1859-1895) - Deforzh, H. V. (History of science and technology, 2018)
The article is devoted to the analysis of the development of Paleozoology science in the world in the era of the victory of evolutionism (1859-1895). Historical, comparative and biographical methods were used while making this article. It allowed to systematize and critically evaluate the used sources, to compare the assessment of the results of activities of different scientists, and to describe those works that contributed to the development of the science of Paleozoology. An analysis of the sources allowed an objective assessment of the contribution from the representatives of different countries to the development of the science of Paleozoology. The merits of our domestic zoologists in the marked process are shown. The multi-vector activity of the Kovalevskys brothers and M.V. Pavlova was analyzed in the context of the theory of evolution development. Based on the comparison of assessments made by different zoological scientists regarding the development of Paleozoology, the role of these scientists in solving evolutionary issues is shown. It is established that the development of the science of Paleozoology quickly found support from the evolutionists of the second half of the nineteenth century thanks to their personal contribution. This analysis enabled to draw the paths of development in both Paleozoology and Evolutionism in general. The victory of evolutionism was not simultaneous; this victory went a long and painful way of rejection and ruthless criticism. And it was the eminent scientists paleozoologists who played a significant role in the formation and strengthening of evolutionary theory in the world. They are such scholars as: Austrian geologist and paleontologist Melchior Neumayr, French paleontologist and geologist Albert Gaudry, Swiss zoologist and paleontologist Ludwig Rutimeyer, American naturalist, paleontologist and comparative anatomist Edward Соре, American paleontologist Othniel Marsh, German geologist, paleontologist and mineralogist Karl Zittel, American geologist and paleontologist Henry Osborn, and many others. The article analyzes the works of these scientists, thanks to which paleontology was able to separate from geology, since for a long time paleontology was a “helper”, “maid” of geology. This separation later contributed to the division of paleontology into paleozoology itself and paleobotany. The use of the biographical method made it possible to consider the persons of evolutionary paleozoologists as separate individuals, which made it possible to evaluate their contribution to the development of the theory of evolution, to re-evaluate their scientific achievements.